2007
DOI: 10.1007/s11908-007-0032-1
|View full text |Cite
|
Sign up to set email alerts
|

Nasal colonization with methicillin-resistant Staphylococcus aureus: Clinical implications and treatment

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) has become an increasingly important pathogen during the past 30 years, and infections due to MRSA are associated with substantial morbidity and mortality. Despite intensive infection control measures, the prevalence of MRSA has increased significantly, and the organism has become endemic in many hospitals worldwide. Asymptomatic nasal carriage of MRSA has been identified as a major risk factor for subsequent S. aureus infection in multiple settings and popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…aureus may lead to a higher probability of developing infections. Indeed, it has been previously shown that in approximately 65% of the cases, genetic similarity between the colonizing and invasive strains can be demonstrated [ 3 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…aureus may lead to a higher probability of developing infections. Indeed, it has been previously shown that in approximately 65% of the cases, genetic similarity between the colonizing and invasive strains can be demonstrated [ 3 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aerosolized vancomycin has been shown to eliminate tracheal MRSA colonization, although it carries a risk of bronchospasm 44. This practice has been discouraged by the United States Centers for Disease Control and Prevention (CDC) due to the potential for inadvertent ingestion of antibiotics and the subsequent selection of vancomycin‐resistant enterococci 45, 46. Some authors have advocated the addition of a topical skin disinfectant for long‐term eradication,43 arguing that failure to prevent recolonization with MRSA may indicate the presence of extranasal colonization at sites such as the perineum or axilla.…”
Section: Discussionmentioning
confidence: 99%